A novel flexible fiber-shaped dual-ion battery with high energy density based on omnidirectional porous Al wire anode. (June 2019) - Song, Chenhui; Li, Yongpeng; Li, Hui; He, Tao; Guan, Qun; Yang, Jie; Li, Xuelian; Cheng, Jianli; Wang, Bin
Abstract: Fiber-shaped dual-ion batteries (FSDIBs) are one of the promising flexible energy storage candidates for wearable electronics owing to their one-dimensional structure, good flexibility and high energy density. To the best of our knowledge, the fabrication of the FSDIBs has not been reported yet. One of the main challenges is to find the appropriate one-dimensional electrode with high capacity, high flexibility and good structure stability under different bending states and in reversible cycle processes. Herein, we report a proof of concept experiment on designing FSDIBs for the first time with high energy density, good reversibility and high cycle stability, which consists of the omnidirectional porous Al wire as the anode and the graphite on the Al wire as the cathode. The assembled battery shows high mass specific energy density of 173.33 Wh kg −1 based on the total mass of the two electrodes (volumetric specific energy density of 10.4 mWh cm −3 ) and excellent flexibility under different bending states. The proposed mechanism is clearly revealed by the in-situ XRD measurements and in-situ Raman spectroscopy, showing that the PF6 − anions are reversibly intercalated/de-intercalated into/from graphite interlayers in the charge/discharge processes to a large extent. Graphical abstract: A proof of concept experiment on designing fiber-shaped dual-ion batteries (FSDIBs) based on omnidirectional porous Al wire as the anode and the graphite as the cathode, has been reported for the first time with good reversibility and high cycle stability.Image 1 Highlights: Omnidirectional porous Al wire was used as anode materials for fiber-shaped dual-ion batteries. The dual-ion batteries show high energy density and excellent flexibility. Reaction mechanism was studied by using in-situ characterization.